A physiological investigation of the adaptive significance of juvenility in Pennantia corymbosa Forst : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Botany at Massey University - Hollows, David Grant (Massey University, 1978)
The responses of the juvenile and adult growth forms of Pennantia corymbosa Forst. to a range of light intensities, leaf temperatures, shoot water potentials and wind velocities were investigated. Results tend to indicate that the small-leafed divaricating juvenile is better adapted to open habitats than the adult. Responses to light intensity were similar for both growth forms. Measurements of photosynthetic rates at various light intensities after pretreatment at low and high irradiances revealed little difference in response between juvenile and adult, with both showing a similar increase in photosynthetic rates and light saturation points after the pretreatment light intensity was increased. Granal stacking in chloroplasts from juvenile and adult leaf palisade was reduced after growth at the higher pretreatment light intensity to the same extent in juveniles and adults. Solarization, despite the presence of a hypodermis, was greater in the adult, while the activity of Ribulose -1,5- diphosphate carboxylase was greater in the juvenile. The indication that the juvenile is better adapted to open habitats is also supported by the results of experiments into the response of photosynthetic rates to a range of temperatures. The data revealed a higher mean temperature optimum for the juvenile than for the adult leaves (21°C c.f. 18°C). The hypothesis that the juvenile might be better adapted to edaphic water stress was tested by withholding water for 14 days and measuring the rates of photosynthesis and transpiration as shoot water potential decreased. Rates of photosynthesis and transpiration declined in both juvenile and adult leaves as shoot water potential decreased. However, the juvenile was able to maintain a higher rate of photosynthesis at comparable low water potentials than the adult which indicates that the juvenile is the more drought tolerant of the two. Leaves of the juvenile also retain water better than those of the adult under moderately windy conditions. When plants were grown in a wind tunnel at wind speeds of up to 12 m secˉ¹ stomatal closure (as measured using a leaf diffusion resistance meter) occurred at lower wind speeds in the juvenile than the adult leaves. The results obtained during this investigation thus support the hypothesis that the small-leafed divaricating juvenile of Pennantia is better adapted to a dry, exposed habitat than is the large-leafed orthotropic adult.
Keywords: New Zealand Trees; Growth (Plants)